Menggagas nilai - nilai multikulturalisme dalam mengatasi permasalahan dunia pendidikan - Trisiana, Anita - (Widya Wacana: Jurnal Ilmiah, 2011)
Abstraksi : To resolve urrent issue, education has to be understood as societal responsibility,encompassing governments, families, communities and organization, and multicultural education.  It requires commitment and participation of all.  That all element of communities should be regarded as “educational instruments.  Therefore, the alternative education would be an importantaggenda in order to complete the selection ot the education that have already, available, even certain limited. Keyword : Nilai – nilai Multikulturalisme, Dunia Pendidikan